Mengenal Bakat dan Minat Anak Sejak Dini : Langkah Awal Menuju Pengembangan Potensi Peserta Didik SD Madrasah Ibtidaiyah Negeri 1 Ende - Siprianus Se’e; Berty Sadipun; Feliks Welu; Agnes Anjelita Sero (Universitas Kristen Indonesia Toraja, 2024)
This PKM aims to recognize children's talents and interests from an early age as the first step in developing the potential of students at SD Madrasah Ibtidaiyah Negeri 1 Ende. This PKM background focuses on the importance of identifying children's self-potential at elementary school age to help them develop skills and interests that match their respective talents. The methods used in this PKM are interactive presentations, games, and group discussions, interest and aptitude tests. The results of this PKM show that most students have a tendency in certain fields such as art, sports, and science, but not all of their potential can be optimized. Some of the influencing factors are the lack of facilitation and understanding of parents and teachers in detecting and directing children's interests and talents. In conclusion, the introduction and mapping of children's talents and interests needs to be done from an early age to provide more appropriate direction in the development of pesert potential